The monastic product's biography, a sacralization wave - Paquier, Marie-Catherine (Journal of management, spirituality & religion, 2019)
Between its monastic origin and its merchant destination, the monastic product is moving from clergy to laity. What happens to this movement during the purchasing act? Imbued with work on the biography of things, this contextualized question is framed by Kopytoff's theory, and extends it by focusing on the purchase, when clerical marketers meet secular consumers. We mobilize the literature about the sacralization process in consumption, enriched by the concept of communitas. An ethnographic methodology is deployed in the French monastic context and its various sales outlets. Findings show that the purchaser, when buying, is (re)joining communities which possess the sacred communitas characteristics. Incremented to previous work on gift-giving in such a purchase, they enable to show the re-sacralization process of the product. We conclude by replacing the usually linear continuum between sacred and profane statuses by a sinusoidal sacralization wave.